Ліплений посуд із розкопок ділянки валу Більського городища - Гречко, Д.С.; Пеляшенко, К.Ю. (Археологія, 2022)
У статті проаналізовано комплекс місцевої ліпленої кераміки з розкопок на поселенні в урочищі Царина Могила в межах Більського городища в 2016—2017 рр. Завдяки чіткому розмежуванню археологічних шарів удалось розділити, схарактеризувати окремо та зробити зіставлення гончарних традицій періодів до, під час та після зведення фортифікаційних споруд Великого Більського городища. The Bilsk archaeological expedition of the Institute of Archaeology of the National Academy of Sciences of Ukraine explored a part of a rampart of the Great Bilsk hill-fort on the territory of the settlement in the Tsaryna Mohyla tract in 2016—2017. The building was found in the investigated area under the embankment of the rampart. It functioned before the construction of the defensive structures of the Great Bilsk hill-fort and was used as a place for the formation of the ash hill after destruction as a result of a fire. The embankment of the rampart was covered by the layers of the settlement from the inside, which continued to function after its construction. The archaeological layers were quite clearly separated, so during the excavations it was possible to get materials from individual stratigraphic horizons. Most of the finds are represented by local handmade pottery. An analysis of the complex of handmade pottery from individual horizons made it possible to give some conclusions about changes of the inhabitants’ pottery of the settlement in a short period of time (the end of the 7th — the first third of the 5th centuries BC). In general, horizons I—IV are characterized by minimal changes in the local ceramic complex. Materials from the cultural deposits of the pre-fortification period and the time of the creation of the fortifications indicate that the pottery traditions of the local population were transformed slowly and the main form of the complex remained stable. It is indicated by the use of slightly profiled pots as cookingware and most of them had an ornament in the shape of a molded roller on the rim or neck, sometimes on the body. Tableware (bowls, ladles) and containers (very large pots) have polished surfaces and archaic morphological features. There are no forms (jugs, mugs and vessels of small sizes) which are more typical for the Middle Scythian time. Only after the building of fortifications, at the end of the 6th — the first third of the 5th centuries BC (horizon V) more noticeable changes can be traced in the pottery of the population of the Bilsk hill-fort: appearance of cookingware with expressed body profile, disappearance of the ornamentation with molded rollers tradition, the fading of the tradition of polished tableware and containers, disappearance of some groups and the spread of new forms (jugs, mugs and small vessels). Thus, the study of the part of the rampart at the territory of the settlement in the Tsaryna Mohyla tract at the Bilsk hill-fort made it possible to consider a collection of handmade pottery dated from the end of the 7th — the first third of the 5th centuries BC. It was possible to divide these materials into close chronological groups with clear stratigraphy and trace certain changes in the material complex of the end of the Early Scythian / the beginning of the Middle Scythian periods. These results clarify ideas about the development of pottery traditions of the population in the forest-steppe zone between the Dnipro and Siverskyi Donets Rivers at the Scythian time.